Usulan Perencanaan dan Pengendalian Persediaan Obat pada Gudang Farmasi Klinik XYZ dengan Menggunakan Metode EOQ - Ringgo Ismoyo Buwono; Yusuf Priyandari; Wachid Ahmad Jauhari (Performa: Media Ilmiah Teknik Industri, 2014)
Klinik XYS is a company that provides health care services. This health care services include medical care and treatment services. In it’s function as a medical services provider, Klinik XYZ provides a pharmacy services. These services have an important role for the clinic because almost all of health services use pharmaceuticals. In the pharmaceutical activities, this company is still having some problem related to inventory management. From the initial observation,it is found that several types of drugs excess the stock which affect the expiration. Further, several types of drugs are out of stock which may result in reduction of patient services. Based on further observation the excess and the emptiness of drugs caused by company’s inability to control and plan the inventory. Therefore, this study proposes an EOQ method to plan and control the inventory in order to optimize the drug supply